Topical Steroids as Adjunctive Therapy for Bacterial Keratitis: Evidence From a Retrospective Case Series of 313 Cases. Issue 5 (September 2020) - Khoo, Pauline; Cabrera-Aguas, Maria; Watson, Stephanie L.
Abstract : Purpose: The aim of this study was to report topical steroid usage in bacterial keratitis and analyze the effects of steroids on patients' outcomes to the main causative organisms. Design: A retrospective case-series. Methods: This study included all patients with corneal scrape positive bacterial keratitis from January 2012 to December 2016 at the Sydney Eye Hospital, Sydney, Australia. Cases were identified from pathology results and hospital coding, and data collected from medical records. Results: A total of 313 eyes from 308 patients with a mean age of 51 years [interquartile range (IQR) 36–72] were included. Of these patients, 192 (61%) were treated with topical steroids. High-dose steroids were prescribed in 22 (11%) cases, regular-dose in 88 (46%), and low-dose in 82 (43%). The median time until the implementation of steroid use was 4 days (IQR 3–7). Patients prescribed with topical steroids had significantly longer healing times than the "no steroid" group (11 vs 6.5, P < 0.001). Patients with Pseudomonas aeruginosa keratitis and topical steroid use had worse clinical outcomes, with a higher proportion having longer healing times ( P = 0.04) and corneal scarring ( P = 0.02). Conclusions: Adjuvant topical steroid therapy did not affect visual acuity, patient outcomes or the rate of adverse effects but may delay epithelial healing in bacterial keratitis in these patients. Topical steroids may have a differential effect depending on the specific causative organisms; however, a clinical trial is needed to assess this.